THE DATA CENTER CANNOT HOLD: DATA COLONIALISM AND THE “NIMBUS PROJECT” - Gekker, Alex; Kotliar, Dan (AoIR Selected Papers of Internet Research, 2023)
Following the infrastructural turn in media studies with its focus on the material and social practices, this paper offers to reexamine contemporary data colonialism by empirically exploring some of its most crucial infrastructural artifacts – data centers. Particularly, this paper explores six data centers currently built in Israel as part of "Project Nimbus" – a $1.2 billion tender offered by the Israeli government to move its computational infrastructure "to the cloud". The tender was won by Amazon Web Services (AWS) and Google Cloud, and has drawn considerable attention, both due to its high-cost and technical complexity; and due to attempts by these companies' workers to curtail the tech giants' involvement in Israel/Palestine on moral grounds. Power differentials are also present within the Israeli society, as intimate governmental data will be processed and stored by foreign US companies.Based on thematic analysis of local journalistic sources, public officials’ documents, local planning authorities and the tender winners themselves, we delineate the concrete materialization of this cloud infrastructure. We show that the notion of data colonialism is complicated within project Nimbus, when lines blur in terms of whose data is colonized by whom, whose lands are used (and colonized) by these centers, and whose resources (predominantly electricity and water) will be used for their functioning. Thus, this paper offers a more granular understanding of data colonialism, and of the different actors and stakeholders involved in the creation and sustainment of this emerging global regime.